Determination of customer requirement for welding fumes index development in automotive industries by using quality function deployment approach - Hariri, Azian; Azreen, N.; Abdull, Norhidayah; Leman, M; M Yusof, M. Z. (Universiti Malaysia Pahang, 2014)
This paper discusses the determination of customer requirements for the development of a welding fumes index by using a Quality Function Deployment (QFD) approach. A welding fumes index is developed with the objective of enhancing welding workplace safety and health. The index simplifies complex health-hazard issues of welding fumes so that they can be comprehended easily by employees and administrators. Likert scale questionnaires on welder desire to know about the health effects of the various welding fumes that exist in their workplace were distributed among welders in the automotive assembly industry in the state of Pahang, Malaysia. A pilot test of the QFD questionnaire was done (n=11) and Cronbach Alpha analysis is 0.967, which indicates a high level of internal consistency of the questionnaire scale. In the actual sampling (n=32), the results of the questionnaires show that all the customer requirements (irritant effect, sensitizer effects, respiratory system effect, systemic toxin effect, reproductive toxins effect, carcinogen effect, mixture effect) were equally important to the welders. The relationship between the customer (welder) requirement and technical characteristics was established, whereby important technical characteristics were shortlisted (personal sampling 23.0%, multi chemical analysis 20.8%, exposure limit 19.7%, health questionnaire 17.6% and lung function test 14.7%). Development of welding fumes indices according to employee demand will increase knowledge and awareness of occupational safety and health among employees (welders).